Thermal Energy Storage Using Adsorption Processes for Solar and Waste Heat Applications: Material Synthesis, Testing and Modeling - Lefebvre, Dominique (Université d'Ottawa / University of Ottawa, 2016)
As the worldwide energy demand continues to increase, scientists and engineers are faced with the increasingly difficult task of meeting these needs. Currently, the major energy sources, consisting of oil, coal, and natural gas, are non-renewable, contribute to climate change, and are rapidly depleting. Renewable technology research has become a major focus to provide energy alternatives which are environmentally-friendly and economically competitive to sustain the future worldwide needs. Thermal energy storage using adsorption is a promising technology which can provide energy for heating and cooling applications using solar and waste heat sources. The current work aims to improve adsorption systems to provide higher energy outputs and therefore, more economical systems. New adsorbents and operating conditions were tested with the goal of storing the available energy more efficiently. A model was also developed to gain a better understanding of the adsorption system to improve this developing technology.
Keywords: Thermal energy storage; Adsorption